The Intention to Use Accounting Software on SMES for becoming Bankable Company - Mirza M. Ranatarisza; Sri Mangesti Rahayu; Latifah Hanum; Desanti Putri Sekti Ari (International Journal of Organizational Behavior and Policy, 2022)
SME is required to be feasible and bankable to make it easier to get access to funding. Currently, there are many SME that are feasible but not yet bankable. Bankable is closely related to financial management by implementing good bookkeeping by business actors by utilizing accounting software. This study examines the factors that can influence the intention of SMEs in using accounting software based on the Theory of Planned Behavior. The sample in this study was taken by proportional stratified random sampling from the database of the cooperative and micro-business offices, which were divided based on the business area. The finding showed that attitudes and perceived behavioral control affected the intention of SMEs in the intention of using accounting software. At the same time, subjective norms did not have a significant effect on the intention of SME business actors in using accounting software.